An Empirical Analysis of the Demand for Home Loans in Urban India - Fulwari, Archana; Kumar, Jayant (Arthshastra Indian Journal of Economics & Research, 2016)
Housing aspirations of households in India have been on a rise, particularly in the post reforms period, and the role of home loans in meeting these needs cannot be overemphasized. The entry of private financial institutions and banks in a big way after the introduction of economic reforms in India and their aggressive posturing have added further fuel to the demand for housing. The post reforms period has witnessed higher personal disposable incomes, lower inflation rates, lower interest rate regime, and an increased thrust on retail lending by the financial institutions, contributing to the expansion of the housing finance sector. The recent years, however, have witnessed a rise in interest rates and inflation, and a general slowdown of the economy, all of which appear to have impacted the housing finance sector. The present paper attempted to find out the impact of important economic factors on the households' demand for home loans for the period from 1990-1991 to 2014- 2015. The study employed regression analysis to examine the significance of income and interest rates in determining the demand for home loans in urban areas.